An Analysis of English Learning at Kebangsaan Pos Bersih School Malaysia - Denda Suryadien; Hilda Ainissyifa; Nurul Fatonah; Nur Balqis Binti Khairulnizam (Al-Aulad: Journal of Islamic Primary Education, 2023)
The purpose of writing this article is to analyze the main problems faced by students and teachers in learning English at the Sekolah Kebangsaan Pos Bersih elementary school in Malaysia. Assess the effectiveness of learning methods and provide recommendations for English learning strategies. This study used a descriptive qualitative methodology with data collection using interviews, moderate participant observation, documentation and literature review. Data from interviews, observations, documentation and literature reviews will be contrasted to identify consistency and differences in teacher practices in providing language learning infrastructure through comparative analysis, research findings will be strengthened and provide a more holistic picture of the problem under study. The results of the discussion are that the researcher found the problems of students in learning English at the SK Pos Bersih 1) motivation and interest 2) limited understanding of English at the beginning 3) Lack of use of English in daily life 4) lack of confidence when communicating as well as for teachers 1) emphasis on standardized tests 2) High Workload. Then the writing of designing strategic suggestions with literature reviews includes 1) encouraging active student involvement 2) Integration of Educational Technology 3) project-based learning 4) student-centered learning. Keywords: english, low school, learning quality